A randomized, controlled, clinical pilot study assessing the analgesic effect of morphine applied topically onto split‐thickness skin wounds. (19th June 2014) - Zaslansky, Ruth; Ben‐Nun, Ohad; Ben‐Shitrit, Sima; Ullmann, Yehuda; Kopf, Andreas; Stein, Christoph
Abstract Objectives To assess the effect of an opioid administered topically onto a standardized skin wound in patients without significant comorbidity. Findings to date are contradictory, often obtained from multimorbid patients with wounds lacking uniformity. Methods Forty‐four patients undergoing surgery for skin grafting were randomly assigned to receive morphine (0.25, 0.75 or 1.25 mg/100 cm2 wound size) in hydroxyethylcellulose gel or placebo applied onto the excised split‐thickness donor wound at the end of surgery. Pain, supplementary systemic opioids and adverse effects were assessed during the first 24 h after application. Healing was examined when the dressings were removed. Key findings Morphine doses ranged from 0.25 to 5.4 mg (mean 1.93 ± standard deviation 1.34 mg). No differences in pain scores or use of supplementary analgesics were found between the groups. Serious adverse effects did not occur; healing was not impaired. Large intragroup variability was observed for pain scores, wound sizes and supplementary analgesia. Conclusions Patients treated with topically applied morphine gel onto standardized skin wounds did not report lower pain scores compared with placebo‐treated patients. Larger groups would be required to arrive at definitive conclusions. The split‐thickness skin graft model can be used for future research.